Konstruksi Identitas Diri dalam Komik Ruronin Kenshin: Kajian Analisis Wacana Kritis Michel Foucault - Akmal Jaya; Christine J. Mamoto; Sulhiyah Sulhiyah (Faculty of Economics, Law, and Humanities, 2019)
This research aims to investigate how identities are constructed and represented in Rurounin Kenshin (1996). By referring to Foucauldian approach, its believed that identities were formed and defined by contestation of discourses which is entailed by social and cultural values. Since comic has been a material object of this study, Pierce semiotic methods have been used to explore how identities represented by symbol, icon, or index in virtual media. Based on this theory and methodological approach, this research found that discourse of modernity and tradition have constructed an identity which represented by idea, fashion, and technology.